Performance of pile foundation for the civil infrastructure of high speed rail in severe ground subsidence area - Yang, H. W. (Proceedings of the International Association of Hydrological Sciences, 2015)
In this study, the performance of pile foundation is assessed for the 30 km long viaduct bridge structure seating in the ground subsidence area in the central part of Taiwan. The focus of this paper is placed on the settlement behaviour of a continuous 3-span R. C. viaduct bridge supported on piles adjacent to highway embankment. Monitoring data accumulated over the last 12 years indicate that the observed pace of the settlement of the viaduct structure in other sections matches that of the ground. However, the bridge piers adjacent to the embankment have been suffering an additional approximately 1 cm settlement every year since the completion of the embankment construction. It was believed that the piers may suffer from enormous negative skin friction owing to the surcharge from the embankment and groundwater depression. This paper first summarizes the settlement analysis results to quantify the settlement of pile due to regional ground subsidence and the combined effects from ground water fluctuation and embankment surcharge loading. Accordingly, a loading path on P'-q stress space is formulated to illustrate the loading variation subject to the combined loading effects that can explain why the combined effect becoming significant on settlement control for civil infrastructure in ground subsidence area.